Diaphragmatic Excursion and Respiratory Function After the Modified Raj Technique of the Infraclavicular Plexus Block. (1st March 2004) - Dullenkopf, Alexander; Blumenthal, Stephan; Theodorou, Panagiotis; Roos, Justus; Perschak, Henry; Borgeat, Alain
Abstract : Background: The effects of the infraclavicular plexus block using the modified Raj approach on diaphragm and respiratory function have not been investigated. Methods: After obtaining approval of the local ethics committee and written informed consent, 20 patients, scheduled for surgery of the forearm, wrist, or hand were prospectively included. Infraclavicular block was performed using the modified Raj technique with 40 to 50 mL ropivacaine 0.5%. Forced diaphragmatic excursion (DE), vital capacity (VC), first-second forced expiratory volume (FEV1 ), and peak expiratory flow rate (PEFR) were assessed the day before surgery and 30 and 360 minutes after blocks, respectively. Results: There was no significant difference between pre- and postblock values, neither for DE (5.6 ± 1.0 cm before the block, 5.2 ± 1.4 cm 30 minutes after the block, and 5.7 ± 1.4 cm 360 minutes after the block) nor for VC (3.2 ± 0.8 L before the block, 3.1 ± 0.9 L 30 minutes after the block, and 3.0 ± 0.9 L 360 minutes after the block), FEV1 (2.8 ± 0.9 L before the block, 2.8 ± 0.9 L 30 minutes after the block, and 2.7 ± 0.9 L 360 minutes after the block), or PEFR (378 ± 116 L/min before the block, 355 ± 110 L/min 30 minutes after the block, and 364 ± 116 L/min 360 minutes after the block). Conclusion: Infraclavicular block using the modified Raj technique did not interfere with diaphragmatic excursion or respiratory function.